2019
DOI: 10.1039/c9ra08457f
|View full text |Cite
|
Sign up to set email alerts
|

Advances in nanomaterials as novel elicitors of pharmacologically active plant specialized metabolites: current status and future outlooks

Abstract: Advancement in nanomaterials as novel elicitors of plant's specialized secondary metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 118 publications
(170 reference statements)
0
39
0
Order By: Relevance
“…It is accepted that NPs may have both beneficial and harmful effects on plants, in particular depending on the concentration [ 16 ]. Many reports have shown that when used at a lower concentration, NPs can promote plant growth and the production of secondary metabolites [ 17 ]. It may be due to NP interaction with some of the plant cell wall and membrane components [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is accepted that NPs may have both beneficial and harmful effects on plants, in particular depending on the concentration [ 16 ]. Many reports have shown that when used at a lower concentration, NPs can promote plant growth and the production of secondary metabolites [ 17 ]. It may be due to NP interaction with some of the plant cell wall and membrane components [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have shown that when used at a lower concentration, NPs can promote plant growth and the production of secondary metabolites [ 17 ]. It may be due to NP interaction with some of the plant cell wall and membrane components [ 17 ]. The structure of the plant cell wall is consistent with the size of the NPs for entry into the cell where the reactive oxygen species (ROS) accumulation can be triggered [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has previously been observed that different concentrations of nanomaterials could have either a supportive or inhibitive impact on the growth and metabolic pathways of an organism. However, these studies, so far, have been investigated the case of plant cells 3‐5 . It has been reported that nanomaterials as abiotic factors activate the pathways related to the secondary metabolites production in plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies, so far, have been investigated the case of plant cells. [3][4][5] It has been reported that nanomaterials as abiotic factors activate the pathways related to the secondary metabolites production in plants.…”
mentioning
confidence: 99%